Optimal location of thyristor controlled series compensator using sensitivity approach - New, Huang Chin (2014)
The vast development and world globalization had caused the existing power system in most country to hit its bottleneck. In order to sustain the demand, the current power supply will need to be expanded. Due to cost saving from expansion the power system network, the system operator has to allow the system to operate nearer to the system thermal limit and subsequently increase the transmit capacity. The Availability Transfer Capability (ATC) can be increased using Flexible AC Transmission System (FACTS). However, FACTS devices are very expensive and high generation scheduling cost. This project is to focus on how to determine the optimal location to install this expensive FACTS devices. Optimal location of the installation of FACTS devices can be determined using the sensitivity analysis. There are several types of FACTS devices, and Thyristor Controlled Series Capacitors (TCSC) has been selected to use in the project report on account of its overall performance and cost effectiveness to relieve congestion. The scope of this project report will using sensitivity based approach to determine the optimal location of TCSC. MATLAB is used to perform the power flow of the power system and the result is adopted into sensitivity index model. Then the location of the TCSC is determined using the most positive sensitivity index. The simulation is tested using POWERWORLD on chosen 5-bus system, IEEE 14-bus system and also 30-bus system. As a result, the optimal location of TCSC is determined and verified.